Qatar : 2008 Article IV Consultation; Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion;. (IMF Staff Country Reports; Country Report ;, 2009)
Qatar's macroeconomic performance was strong in 2008, notwithstanding the global financial crisis. This 2008 Article IV Consultation discusses that overall real GDP growth is estimated at 16 percent in 2008, driven by expansions in the production of oil, liquefied natural gas, and condensates. Executive Directors have welcomed the authorities' intention to moderate fiscal expansion and broaden the non-oil revenue base over the medium term. They have supported the emphasis on building capacity in infrastructure and easing supply bottlenecks while containing government current expenditure to reduce inflation.